Deuteration enhances catalyst lifetime in palladium-catalysed alcohol oxidation. Issue 10 (4th January 2016) - Armenise, Nicola; Tahiri, Nabil; Eisink, Niek N. H. M.; Denis, Mathieu; Jäger, Manuel; De Vries, Johannes G.; Witte, Martin D.; Minnaard, Adriaan J.
Abstract : The catalyst palladium/2, 9-CD3 -phenanthroline has a 1.8 times higher turnover number than its non-deuterated counterpart in the aerobic alcohol oxidation of methyl glucoside and allows the regioselective oxidation with dioxygen as the terminal oxidant. Abstract : The catalyst palladium/2, 9-CD3 -phenanthroline has a 1.8 times higher turnover number than its non-deuterated counterpart in the aerobic alcohol oxidation of methyl glucoside and allows the regioselective oxidation with dioxygen as the terminal oxidant.